From Getting Ahead to Getting Back on One's Feet: Performing Masculinity as a Self-help Reader. (October 2019) - McLean, Scott; Vermeylen, Laurie
Despite the fact that millions of men engage in self-help reading, there has been little scholarly research about the reception of self-help texts by male readers. We explore how men read self-help books through presenting the results of forty-five qualitative interviews with readers of books in the domains of career and financial success, health and well-being, and interpersonal relationships. Our interviewees expressed awareness of the stigmatized role of the male self-help reader and performed two patterns of masculinity, influenced by hegemonic ideals, within this context: the resourceful man getting ahead in life; and the wounded man getting back on his feet. A small proportion of our interviewees challenged conventional notions of masculinity, demonstrating the potential for men to read self-help books in diverse ways. Our findings shed important insight into how men read self-help books and into the performance of masculinity in the context of such reading.